The Dictionary of Accessible Communication - Hansen-Schirra, Silvia; Abels, Katja; Signer, Sarah; Maaß, Christiane (Frank & Timme, 2021)
Terminology on Accessible Communication has primarily evolved and been published within the borders of a given country with no or only little exchange across these borders. Since English can be regarded as the "lingua franca" of science, this first German-English dictionary of Accessible Communication will help to promote international exchange and an international discourse on this topic by attempting to define concepts that go beyond the scope of a single-country centered approach. The terminological work for this dictionary is based on the German Handbook of Accessible Communication. Most of the handbook's contents are language-independent and applicable to other recipient communities. On the basis of the German terminology, the English equivalents, definitions and explanations were researched. The dictionary contributes to the development of a standardised terminology across languages and cultures.